La nascita della meccanica quantistica - Califano, Salvatore (Studi e saggi, 2018)
Quantum mechanics constituted a great scientific and cultural revolution that profoundly changed our approach to the study of the microscopic and subatomic world. The birth and evolution of the theories of quantum mechanics are revived through the personal and scientific history of the protagonists, their attempts and their working hypotheses, the discoveries, doubts and discussions. The substantially counterintuitive concepts of the new mechanics have redesigned the meaning of our knowledge of the world of atoms; particular attention is then paid to the impact that this new vision of the microscopic world has had on chemistry and our knowledge of the structure and reactivity of atoms and molecules.